Ruralidad y desarrollo en Costa Rica: fracturas, oportunidades y desafíos - Isabel Román-Vega (Universidad Nacional, Costa Rica, 2002)
The objective of this article is to identify the main challenges of rural education in Costa Rica for the new millennium. This analysis is divided into four main themes: 1) the changing rural world, new theoretical and practical referents, 2) changes in the Costa Rican rural setting: a summary of the main tendencies; 3) changes in the rural world as seen in the perspective of regional dynamics; and 4) the challenges of the rural world and education. This work is based on research done by the author within the framework of the project known as State of the Nation in Sustainable Human Development.